Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1464-410x.1993.tb06449.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Treatment of Vesicoureteric Reflux in Transplanted Kidneys

Abstract: Twenty-one patients underwent endoscopic subureteric injection of Polytef paste for the correction of secondary vesicoureteric reflux (VUR) in transplanted kidneys. Ureteroneocystotomy was performed in renal transplants using an extravesical technique in 19 patients and the Leadbetter-Politano technique in 2 cases. Success was achieved in only 6 patients, including the 2 ureters reimplanted according to the Leadbetter-Politano technique. No significant complication relating to the technique was observed. Despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 10 publications
1
4
0
2
Order By: Relevance
“…Therefore, PDS treatment is recommended as preferable to surgical reimplantation [15,16,17]. However, there has only been one report of endoscopic PDS treatment in renal transplant recipients, with a 30% success rate [21]. In our study, the overall success rate of endoscopic treatment using PDS was 63.2%, which is similar to the success rate in pediatric patients with VUR.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, PDS treatment is recommended as preferable to surgical reimplantation [15,16,17]. However, there has only been one report of endoscopic PDS treatment in renal transplant recipients, with a 30% success rate [21]. In our study, the overall success rate of endoscopic treatment using PDS was 63.2%, which is similar to the success rate in pediatric patients with VUR.…”
Section: Discussionsupporting
confidence: 73%
“…Cloix et al. (8) found that in their 21 patients with secondary VUR after transplant, only 30% of patients had resolution of their reflux with subureteric injection of Polytef paste. Similarly, Mallet et al.…”
Section: Discussionmentioning
confidence: 99%
“…and Mallet et al. (24, 25). We estimated the cost of an open procedure to be U$9263.00 compared to U$1947.00 per treatment for the endoscopic procedure.…”
Section: Discussionmentioning
confidence: 87%
“…Although endoscopic treatment has a lower success rate compared to open conventional surgery, it has the advantage of being an outpatient procedure that is minimally invasive with a low morbidity and a lower overall cost (23). This is particularly true in renal transplant patients, as has been demonstrated by Cloix et al and Mallet et al (24,25). We estimated the cost of an open procedure to be U$9263.00 compared to U$1947.00 per treatment for the endoscopic procedure.…”
Section: Discussionmentioning
confidence: 98%